Self-leadership traits of academics to conform to a changing higher education environment - Jooste, K.; Frantz, J. (African journal of health professions education, 2017)
Background. Now, perhaps more than ever, leadership is seen to be associated with those who manage to create and promote a compelling and meaningful sense of their own values and identity that is demonstrated in the traits they portray to followers. In higher-education sectors, ‘leadership at all levels’ refers to both those in formal roles, such as departmental chairpersons, and those in informal roles, such as postgraduate-degree supervisors or mentors. Objectives. To explore academics’ experiences of their self-leadership traits in a higher-education institution in a changing educational environment. Methods. A qualitative, exploratory, descriptive and contextual research design was followed. The study population consisted of senior academics in departments in the Faculty of Community and Health Sciences at a residential university in South Africa. Purposive convenience sampling was used to include 10 available participants, all vice deans or heads of department, after which data saturation occurred. Individual interviews were conducted that lasted around approximately 45 minutes. The data were analysed using open coding. Results. Five themes emerged around leadership: its development over time; that it can be earned though different means; that it is influenced through personal experience; the role of role models; and environmental encouragement. Conclusion. The study findings indicated different views on the development of leadership skills. Participants commented on the importance of a complex blend of competencies needed by leaders. A number of suggestions were put forth on how to develop leadership skills.